Drug Delivery: Shuttle‐Mediated Nanoparticle Delivery to the Blood–Brain Barrier (Small 6/2013). Issue 6 (15th March 2013) - Guarnieri, Daniela; Falanga, Annarita; Muscetti, Ornella; Tarallo, Rossella; Fusco, Sabato; Galdiero, Massimiliano; Galdiero, Stefania; Netti, Paolo A.
<x xml:space="preserve">Abstract</x> Viruses are formidable micromachines able to overcome potent physiological barriers and to penetrate deep inside our tissues. Following a bioinspired approach, S. Galdiero, P. A. Netti, and co‐workers created a novel class of nanoparticles able to cross the vascular brain endothelium membrane, obtained by decorating their surface with the membranotropic gH625 peptide sequence derived from the glycoprotein gH of Herpes simplex type 1 virus envelope. This promising strategy, described on page 853, paves the way for designing delivery systems to improve administration of therapeutical compounds to the brain. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>